Implementation of Pekanbaru City Policy on Public Order and Community Tranquility - Syaprianto, Syaprianto; Afrizal, Afrizal; Siska, Lira Tri (UIR Press, 2023)
Public order is an orderly situation with principles, politeness, and discipline to achieve a peaceful and serene atmosphere. The existence of policies regulating public order in Pekanbaru City is undoubtedly an essential and binding thing for the population and the city's development; it is expected to create security and comfort for the community in carrying out life for public order. The implementation of public order is still an unsolved problem in Pekanbaru City, so there are still violations of public order, one of which is the emergence of business places that are used as places of prostitution even though the government has implemented regional regulation number 13 of 2021 concerning public order and public peace. The purpose of this research is to find out the implementation of the Pekanbaru city policy on public order and public peace and the inhibiting factors in policy implementation. This research uses a qualitative method by interviewing research informants in depth. The theory used in this research is Edward III's implementation theory, which includes indicators of communication, resources, disposition, and bureaucratic structure. Based on the results of the study, the Implementation of Pekanbaru City Regional Regulation number 13 of 2021 concerning public peace and order can be concluded that the Implementation of the Policy has been carried out, but not optimally. This is because there are still places of business that violate these regional regulations. The obstacle in this research is the need for more human resources needed to implement the policy.